2019
DOI: 10.3390/su11030630
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Releasing Greenbelt Restrictions on Land Development in the Case of Medium-Sized Cities in Korea

Abstract: Many metropolitan areas around the world aim to control urban growth with a view to achieving efficiency and containing urban problems. Among many urban growth policy tools, the green belt (GB) policy is known as the most rigid and strongest. However, there has been no study on the consequences when GB restrictions are completely removed. The primary purpose of this study is to analyse the spatial effects of greenbelt removal on land development in Korea’s medium-sized cities between 2000 and 2017. To do so, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(68 reference statements)
0
5
0
2
Order By: Relevance
“…These strategies will make up the significant impacts on the prospect of greenbelt. Kim et al (2019) have mentioned that the effectiveness of a greenbelt strategy is controversial due to its different effects. Some researchers have claimed that the proper strategies in greenbelt planning can result in sprawl restriction (Amati and Yokohari 2006; Woo and Guldmann 2011), while other researchers have noted that the unsuitable greenbelt strategies can encourage leapfrog development (Jun and Hur 2001;Dawkins and Nelson 2002;Bae and Jun 2003;Ogura 2010).…”
Section: Developing Key Strategies For Greenbelt Planning In Mashhadmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies will make up the significant impacts on the prospect of greenbelt. Kim et al (2019) have mentioned that the effectiveness of a greenbelt strategy is controversial due to its different effects. Some researchers have claimed that the proper strategies in greenbelt planning can result in sprawl restriction (Amati and Yokohari 2006; Woo and Guldmann 2011), while other researchers have noted that the unsuitable greenbelt strategies can encourage leapfrog development (Jun and Hur 2001;Dawkins and Nelson 2002;Bae and Jun 2003;Ogura 2010).…”
Section: Developing Key Strategies For Greenbelt Planning In Mashhadmentioning
confidence: 99%
“…Currently, greenbelt policies have been adopted by many cities around the world (Yokohari et al 2000;Kuhn 2003;Fung and Conway 2007). Recently, Kim et al (2019) have noted that the effectiveness of the greenbelt plan may also depend on the stage of urban development. Indeed, the greenbelt affects the shape of cities by surrounding urban patches with a belt of agricultural or open areas, enforcing on land development from the city edges to remote suburb areas (Wang et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There has been disagreement in previous studies on whether greenbelts positively or negatively affect land prices. Furthermore, it is difficult to conclude whether greenbelts are an effective policy tool or not, because the effectiveness of the greenbelt policy depends on local conditions of the land market, such as the size of developable lands between the core city and the greenbelt [11]. Although the greenbelt provides plenty of amenities for people, its effectiveness as a policy tool is disappearing [12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bengston and Youn concluded that in comparison to London, Seoul's urban containment policy has largely failed to keep development from invading the Capital Region beyond the green belt. The intense pressure of exceptionally rapid urban growth has been too much to contain [26].…”
Section: Introductionmentioning
confidence: 99%